Doktorat jako stopień naukowy: geneza, znaczenie, kontrowersje - Gromkowska-Melosik, Agnieszka (Studia Edukacyjne, 2020)
The text is devoted to the significance and genesis of doctoral degree and historical contexts of doctorate’s award ceremony. Next, the statistics on doctorate recipients by broad field of study and sex has been analysed. Also the types of doctorate has been described. The ultimate conclusion refers to the conviction that, notwithstanding the raised controversy, obtaining a doctoral degree is a turning point in the academic and socio-professional career of young people.